2020
DOI: 10.1097/brs.0000000000003546
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of a New Muscle Sparing “C3 Dome-Hybrid Open-Door Laminoplasty”

Abstract: Study Design. Retrospective case series to investigate the result of a new C3 dome-hybrid open-door laminoplasty technique. Objective. This study reports the design and feasibility of a new hybrid laminoplasty technique aimed to reduce the complications of the conventional laminoplasty, with the incorporation of C3 dome-osteotomy, an open-door C4–6 instrumented laminoplasty and C7 cephalad dome-osteotomy. Summary of Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…An additional suggestion is that performing undercutting "dome" laminectomy at C3 rather than laminoplasty provides superior muscular and ligamentous preservation at the rostral end of the laminoplasty. Liu et al [36] reported decreased loss of lordosis when employing C3 partial "dome" laminectomy. However, only 26 patients were included in this study, which did not include a comparison group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional suggestion is that performing undercutting "dome" laminectomy at C3 rather than laminoplasty provides superior muscular and ligamentous preservation at the rostral end of the laminoplasty. Liu et al [36] reported decreased loss of lordosis when employing C3 partial "dome" laminectomy. However, only 26 patients were included in this study, which did not include a comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…When using skip-level plating, another group reported improved postoperative lordosis when plating at C4 and C6 rather than C3 and C5 [35]. Finally, another group reported good clinical outcomes using partial undercutting ("dome") laminectomy at C3 above C4 laminoplasty instead of C3 laminoplasty, but their study did not include a comparison group [36].…”
Section: Introductionmentioning
confidence: 99%